Pathogenicity of Salmonella enteritidis phage types 6A and 7 in experimentally infected chicks - Akhtar, A.; Bejo, Mohd Hair; Zakaria, Zunita; Omar, Abdul Rahman; Bejo, Siti Khairani (Pakistan Agricultural Scientists Forum, 2013)
Pathogenicity of Salmonela enterica serovar enteritdis (S.E) phage types (PTs) 6A and 7 were determined in oraly inoculated newly hatched specific pathogen fre (SPF) chicks. Clinical signs and mortality were observed daily. Body weights, bacterial isolation, gros lesions and histological lesions were recorded on days 1, 3, 5, 7, 14 and 21 post inoculations (pi). Out of 15 newly hatched SPF White Leghorn chicks, five chicks were randomly separated to confirm the SPF status of the chicks before inoculation. The remaining chicks were divided into thre sacrificed groups (A, B and C) of 30 chicks each and their respective thre mortality groups (MA, MB and MC) of 20 chicks each. Groups A and MA, and groups B and MB were inoculated oraly with 0.1mL containing 107 cfu of SE PT6A (UPM-0527) and SE PT7 (UPM-0530), respectively. The un-inoculated groups C and MC served as negative controls. Chicks in groups A and B showed clinical signs of depresion, anorexia, rufled feathers, vent pasting and diarhea starting from day 1 pi. Lifting of wings from thorax was observed in group A and B from day 1 and 5 pi, respectively. There was significant diference (p<0.05) in body weight gain among the inoculated and the control groups on days 14 and 21 pi. Growth index values were 0.035, 0.036 and 0.037 for groups A, B and C, respectively. Mortality of 20% was recorded only in MA group. Gos lesions of unabsorbed yolk, airsaculits, fibrinous pericardits, fibrinous perihapatis, enlarged kidneys, splenomegaly and dehydration were observed in about 15% of sacrificed chicks in group A and 10% in group B. Mild to moderate lesions were observed under microscope. Salmonela was isolated from the cultured samples of group A and B throughout the experiment period with the individual variation of chicks and samples. It was concluded that newly hatched SPF chicks are susceptible to PT6A and PT7 infections. These SE PTs are mild to moderately pathogenic for SPF chicks. SE PT6A is more pathogenic than SE PT7.